EFFECT OF AUDIT STANDARD COMPLIANCE, DIGITAL AUDIT, TIME BUDGET PRESSURE ON RED FLAG AND AUDIT DELAY - Oktaviyanto, Nanda; Ratnawati, Tri (JEA17: Jurnal Ekonomi Akuntansi, 2023)
The purpose of this study was to test the ability of red flags as mediation of audit delay. This research was conducted because it is to test that red flags are signs of fraud or indications of fraud that auditors must pay attention to avoid audit delay. A total of 40 questionnaires were distributed to auditors from junior to partner level, but only 37 questionnaires were returned and processed. Hypothesis testing in this study uses analysis with the SmartPLS application with the Outer Model and Inner Model Test. The results showed that red flag is a mediation showing that red flag has a significant effect on audit delay. This shows that in the presence of red flags, auditors must be more careful and take immediate action to prevent audit delay through the variables tested, namely, Audit Standards Compliance, Digital Audit, Time Budget Pressure. Audit delay can occur due to red flags so that the auditor's decision to make a decision to provide an opinion will take a longer time.